Patient-blood management for COVID19 convalescent plasma therapy: relevance of affinity and donor–recipient differences in concentration of neutralizing antibodies. (July 2021) - Focosi, Daniele; Maggi, Fabrizio; Franchini, Massimo; Aguzzi, Adriano; Lanza, Maria; Mazzoni, Alessandro; Menichetti, Francesco
Abstract: Background: Coronavirus disease 2019 (COVID-19) convalescent plasma (CCP) is being extensively investigated as a treatment, with mixed results to date. Overall, there has been a generalized lack of appropriateness in prescriptions, which, in the field of transfusion medicine, is termed patient-blood management. Objectives: We aimed to separate study design variables that could affect clinical outcome after CCP therapy. We focus here on variables such as pretransfusion antibody testing in recipients, dose adjustments and antibody affinity measurements. Sources: We searched PubMed and preprint servers for relevant preclinical and clinical studies discussing each of these variables in the field of CCP therapy. Content: We show evidence that neglecting those variables has affected the outcomes of the vast majority of CCP clinical trials to date. Implications: A better understanding of such variables will improve the design of the next generation of CCP clinical trials. This will likely lead to better clinical outcomes and will minimize risks of immune evasion from subneutralizing doses of neutralizing antibodies.